Evaluation of PEG-L-asparaginase in asparagine suppression and anti-drug antibody development in healthy Beagle dogs: A multi-phase preclinical study. (August 2022) - Feenstra, L.R.; Gehring, R.; van Geijswijk, I.M.; König, T.; Prinsen, H.C.M.T.; Vandemeulebroecke, K.; Lammens, T.; Krupa, A.; Teske, E.
Abstract: L -asparaginase is a frequently used drug in the treatment of canine malignant lymphoma. Since production and availability of native E. coli -derived L -asparaginase are limited, PEG-L-asparaginase (PEG-ASP) is an alternative. However, recommended doses and dosing intervals are mainly empirically determined. A multi-phase clinical dose-finding study with seven healthy Beagle dogs was conducted to find the minimum effective dose and, potentially, a dosing interval for PEG-ASP in dogs. Plasma concentrations of amino acids and PEG-ASP activity were measured at various time points after administration of different doses of PEG-ASP. Anti-PEG and anti-asparaginase antibody titres were measured. Administration of 10 IU/kg PEG-ASP resulted in asparagine depletion in all dogs, albeit for various durations: for 9 days in all dogs, 15 days in five dogs, 21 days in three dogs and 29 days in one dog. Asparagine suppression occurred at PEG-ASP plasma concentrations < 25 IU/L. Subsequent administrations of a second and third dose of 20 IU/kg and 40 IU/kg PEG-ASP resulted in asparagine suppression at < 9 days in five dogs, accompanied by the development of antibodies against PEG and L -asparaginase. Two dogs with prolonged asparagine suppression after the second and third administration did not develop antibodies. Marked individual variation in the mechanism and duration of response to PEG-ASP was noted. Antibody formation against PEG-ASP was frequently observed and sometimes occurred after one injection. This study suggests that PEG-ASP doses as high as the currently used dose of 40 IU/kg might not be needed in treatment of canine malignant lymphoma. Highlights: Canine polyethylene glycol (PEG) L -asparaginase activity varied widely. There was variation in the mechanism of asparagine plasma suppression. Asparagine suppression occurred at low L -asparaginase concentrations. Antibodies against asparaginase were common and could occur after one injection.